2019
DOI: 10.1176/appi.ps.201800504
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antipsychotic Polypharmacy and Outcomes for People With Serious Mental Illness in England

Abstract: Objective-Although UK and international guidelines recommend monotherapy, antipsychotic polypharmacy in people with serious mental illness is common in clinical practice. However, empirical evidence on its effectiveness is scarce. The effectiveness of antipsychotic polypharmacy relative to monotherapy is estimated in terms of health care utilization and mortality. Methods-Primary care data from the Clinical Practice Research Datalink, hospital data from the Hospital Episodes statistics and mortality data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 25 publications
2
47
0
1
Order By: Relevance
“…In line with recent studies in British and Finnish patients with schizophrenia showing good survival rates for antipsychotic combination therapy, antipsychotic polypharmacy performed well in the current primary and secondary analyses (with slightly weaker results in sensitivity analyses). 14,29 In particular, the combinations of clozapine with quetiapine, clozapine with olanzapine, clozapine with aripiprazole and quetiapine with risperidone seem promising treatment options based on our data. The current study population consisted of relatively severely affected patients who possibly require treatment with multiple antipsychotics for optimal occupation of the D2 and 5HT2a receptors.…”
Section: Discussionmentioning
confidence: 88%
“…In line with recent studies in British and Finnish patients with schizophrenia showing good survival rates for antipsychotic combination therapy, antipsychotic polypharmacy performed well in the current primary and secondary analyses (with slightly weaker results in sensitivity analyses). 14,29 In particular, the combinations of clozapine with quetiapine, clozapine with olanzapine, clozapine with aripiprazole and quetiapine with risperidone seem promising treatment options based on our data. The current study population consisted of relatively severely affected patients who possibly require treatment with multiple antipsychotics for optimal occupation of the D2 and 5HT2a receptors.…”
Section: Discussionmentioning
confidence: 88%
“…However, in the fully adjusted model, which used standard propensity scores to reduce the effect of confounding by indication, the estimates were no longer statistically significant . In line with this, another large UK study, this time drawing data from primary care medication records found that relative to monotherapy, antipsychotic polypharmacy was not associated with mortality . Likewise, a population‐based nested case‐control study from China concluded that antipsychotic polypharmacy did not contribute to the excess mortality observed in patients with schizophrenia compared with the background population …”
Section: Antipsychotic Polypharmacymentioning
confidence: 90%
“…Clinical follow‐up studies point to the fact that, in general, patients treated with antipsychotic polypharmacy when dismissed from the hospital are more likely to be readmitted compared with patients prescribed antipsychotic monotherapy, also when adjusting for confounding by indication . This seems to be in contrast to evidence from larger register‐derived data sets which describe either no association of antipsychotic polypharmacy with risk of hospital admission or perhaps a protective effect regarding risk of rehospitalization . In general, antipsychotic polypharmacy has been found to be associated with higher total costs of treatment including longer duration of inpatient stay …”
Section: Antipsychotic Polypharmacymentioning
confidence: 93%
See 1 more Smart Citation
“…Both experts, by experience, have felt part of the team and have co-authored four articles during the project, with other research papers and dissemination activities to follow. [39][40][41][42] Discussion and conclusions…”
Section: Study Resultsmentioning
confidence: 99%